Montane bias in lowland Amazonian peatlands: Plant assembly on heterogeneous landscapes and potential significance to palynological inference - Householder, John Ethan; Wittmann, Florian Karl; Tobler, Mathias W.; Janovec, John P. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2015)
Past temperature changes in tropical mountain regions are commonly inferred from vertical elevational shifts of montane indicator taxa in the palynological record. However temperature is one of several abiotic factors driving the low-elevational limits of species and many montane taxa can occur in warmer lowlands by tracking appropriate habitat types, especially highly flooded wetlands. In this paper we explore ways in which lowland habitat heterogeneity might introduce error into paleo-temperature reconstructions, based on field data of seven modern peatland vegetation communities in the southern Peruvian Amazon (~. 200. masl). Peat-rich substrates are common edaphic transitions in pollen cores and provide detailed records of past vegetation change.The data show that indicators of modern peatlands include genera with montane as well as lowland distributions, while indicators of surrounding forests on mineral substrates have predominantly lowland distributions. Based on family-level analyses we find that modern peatland vegetation communities have taxonomic compositions appearing to be 389. m to 1557. m (mean. =. 1050. ±. 391. m) above their actual elevations due to a high abundance and number of families with high elevation optima.We interpret the relatively higher prevalence of montane elements in modern peatlands as habitat tracking of a conserved montane niche on heterogeneous lowland landscapes. We suggest that both high moisture availability and stressful edaphic conditions of peatland habitat may explain the montane bias observed. To the extent that fossilization provides a better record of past vegetation that occurred proximate to the site of deposition, we suggest that habitat tracking of montane elements may introduce a cool bias in lowland paleo-temperature reconstructions based on pollen proxies. © 2015 Elsevier B.V.
Keywords: Climate Variation; Elevation; Field Survey; Fossilization; Heterogeneity; Lowland Environment; Montane Forest; Paleotemperature; Palynology; Peatland; Reconstruction; Taxonomy; Temperature Gradient; Vegetation Cover; Amazonia